PELATIHAN PEMBUATAN KONTEN DIGITAL DALAM UPAYA PROMOSI DAN PEMBELAJARAN PADA PONDOK PESANTREN JAISYUL QUR’AN - Rita Destiwati; Diah A. Esfandari; Caecillia Menzelthe (KRIDA CENDEKIA, 2025)
In the increasingly advanced digital era, Islamic boarding schools (pesantren) in Indonesia face the challenge of remaining relevant and competitive, both in terms of promotion and education. Digital content creation training becomes a strategic solution in this effort, in which pesantren can utilize various digital platforms such as social media, websites, and mobile applications to promote religious messages and provide engaging and interactive learning materials. This training is designed to provide practical skills to 29 teachers at Pondok Pesantren Jaisyul Quran in producing high-quality digital content. These skills include video production, graphic design, creative writing, and effective digital marketing strategies. The content produced from this training is expected to support two main objectives: first, to enhance the image of Pondok Pesantren Jaisyul Quran as a modern and adaptive institution to technological developments; second, to provide learning materials that are more engaging and easier for the students to understand. With the presence of high-quality digital content, the pesantren can attract more prospective students and donors, as well as expand its network of cooperation with various parties. Post-training, 29 participants showed significant improvement in cognitive and affective aspects. Participants not only understood the importance of engaging and educational content, but they also became aware of the use of social media content as teaching materials and school promotion. In addition, the participants were very active and enthusiastic in practicing the creation of digital content as directed by the speaker. Even the participants expressed a desire for further training on digital content creation.